Voronoi Tree Maps with Circular Boundaries - Ahmed, Abdalla G. M. (CGVC'18: Extended Abstracts of the Computer Graphics and Visual Computing, 2018)
Voronoi tree maps are an important milestone in information visualization, representing a substantial advancement of the original tree maps concept. We address a less-studied variant of Voronoi tree maps that uses multiplicative-weighted Voronoi diagrams. We highlight the merits of this variant, and discuss the difficulties that might have discouraged further exploration, proposing insights for overcoming these difficulties.